CFD investigation of a vertical annealing furnace for stainless steel and non-ferrous alloys strips – A comparative study on air-staged & MILD combustion. (1st February 2022) - Mayrhofer, Markus; Koller, Michael; Seemann, Peter; Prieler, Rene; Hochenauer, Christoph
Highlights: Numerical investigation of a vertical muffle type furnace. Validation with transient experimental data. Heat transfer under flameless and air-staged combustion. Evaluation of the thermal load on furnace components. Prediction of the transient heating process of the steel. Abstract: A 3D CFD modelling approach of a vertical high temperature furnace in a bright annealing line for stainless steel is presented in this study. The observed line has a maximum production rate of 4.5 tonnes per hour and an overall thermal input of 1.5 MW which is provided by gas burners. The muffle furnace is an indirect heating system equipped with flameless burners, which can operate at nominal power and in off-design. The burners are arranged in four heating zones, which can be controlled separately. Pure hydrogen is used inside the muffle as protection gas around the metal. The metal strip is modelled as a highly viscous fluid with temperature-dependent properties including the specific heat, thermal conductivity and emissivity. Good accordance with measurements from an industrial line was achieved with several values from furnace thermocouples and the transient heating characteristic of a selected strip dimension, thus, demonstrating the applicability of the CFD model for the present investigations. Further simulations were performed with air-staged combustion for an evaluation of combustion and furnace efficiency as well as the thermal load on the furnace's components. It was found that the efficiency decreased by about 0.5% using flameless combustion. The results also showed a decreased peak temperature of about 1155 °C and a reduced heat flux of about 23.3 kW/m 2 (−5%) on the muffle when Moderate or Intense Low oxygen Dilution (MILD) combustion is applied. The present methodology presents an efficient approach for investigation and optimization of indirect heated muffle type furnaces.